2022
DOI: 10.1155/2022/5780964
|View full text |Cite
|
Sign up to set email alerts
|

Corni Fructus Alleviates UUO-Induced Renal Fibrosis via TGF-β/Smad Signaling

Abstract: Renal fibrosis is a type of chronic kidney disease (CKD) induced by infiltration of inflammatory cells, myofibroblast accumulation, and ECM production in the kidney. From a long time ago, Corni Fructus (CF) is known to supplement the liver and kidney with its tepid properties. In this study, we investigated the renal protective mechanism of CF, which is known to supplement the kidney, in rat model of unilateral ureteral obstruction (UUO). After inducing UUO through surgery, the group was separated ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…7-O-galloyl-D-sedoheptulose reduced the renal protein expression of NOX-4 and one of the subunits of NADPH oxidase-p22(phox) [ 56 ], while the administration of loganin led to a significant decrease in the expression of both NOX-4 and p22(phox) in the liver of diabetic db/db mice [ 57 ]. Comparable results were obtained among others by Lee et al [ 58 ], Chen et al [ 59 ], and Fang et al [ 60 ].…”
Section: Discussionsupporting
confidence: 52%
“…7-O-galloyl-D-sedoheptulose reduced the renal protein expression of NOX-4 and one of the subunits of NADPH oxidase-p22(phox) [ 56 ], while the administration of loganin led to a significant decrease in the expression of both NOX-4 and p22(phox) in the liver of diabetic db/db mice [ 57 ]. Comparable results were obtained among others by Lee et al [ 58 ], Chen et al [ 59 ], and Fang et al [ 60 ].…”
Section: Discussionsupporting
confidence: 52%
“…The Recombinant Purinergic Receptor P2Y(P2Y12) inhibitor clopidogrel attenuates renal fibrosis by inhibiting the transition of macrophages to myofibroblasts via the TGF-β/Smad3 signaling pathway [ 64 ]. Capsaicin attenuates renal fibrosis by inhibiting TGF-β1-Smad2/3 signaling pathway, delaying myofibroblast activation and protecting renal tubular epithelial cell phenotype changes [ 65 ], Corni Fructus alleviates renal fibrosis by inhibiting oxidative stress in UUO and modulating the TGF-β1/Smad pathway [ 66 ]. Similarly, Nootkatone can also exert anti-fibrotic effects in a mouse model of unilateral ureteral obstruction by regulating the Tgf-β/Smad signaling pathway [ 67 ].…”
Section: Treatment Of Renal Interstitial Fibrosis In Obstructive Neph...mentioning
confidence: 99%
“…1) The TGF-β1 exerts its effects on target genes, mainly through downstream phosphorylation of Smad 2/3 proteins, and their role in the transcriptional regulation of ECM genes such as collagen type 1 (COL1A1), fibronectin, and tissue inhibitor of metalloproteinase 1 (TIMP1), which ultimately result in the development and progression of fibrosis. 5,8) In addition, TGF-β1 can signal through Smad-independent signaling cascades. 9) Several studies confirmed that the mitogen-activated protein kinase (MAPK) signaling pathways are directly activated by TGF-β1.…”
Section: Introductionmentioning
confidence: 99%